2023
DOI: 10.7759/cureus.37487
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Hyperglycemia in COVID-19

Abstract: Diabetes mellitus (DM) is one of the most common chronic metabolic disorders worldwide, which increases the risk of common and opportunistic infections. Following the coronavirus disease 2019 (COVID-19) pandemic, a higher incidence rate, more severe forms of the disease, and exacerbation of hyperglycemia and its complications have been observed in patients with DM. Moreover, stress-induced hyperglycemia has been observed in many hospitalized nondiabetic patients after contracting COVID-19. Hyperglycemia worsen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
2
3
0
2
Order By: Relevance
“…We observed viral RNA and S-protein positivity in different organs till 21 days, with a peak at 14DPI. Our findings are consistent with some clinical reports showing ocular manifestation in patients varied from 15 days to two months post-infection [ 55 , 56 ]. Moreover, a study has demonstrated the presence of viral RNA in ocular swabs from a COVID-19 patient with ocular manifestations by day 21–27 from the onset of symptoms [ 57 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We observed viral RNA and S-protein positivity in different organs till 21 days, with a peak at 14DPI. Our findings are consistent with some clinical reports showing ocular manifestation in patients varied from 15 days to two months post-infection [ 55 , 56 ]. Moreover, a study has demonstrated the presence of viral RNA in ocular swabs from a COVID-19 patient with ocular manifestations by day 21–27 from the onset of symptoms [ 57 ].…”
Section: Discussionsupporting
confidence: 93%
“…Diabetes is recognized as a comorbidity associated with increased morbidity and mortality during SARS-CoV-2 infection. High expression of ACE2 in diabetics has been reported to cause severe infection in these patients [ 56 ]. Many clinical studies including meta-analyses have reported increased incidence of SARS-CoV-2 infectivity, disease severity, and mortality associated with COVID-19 in diabetics as compared to non-diabetics individuals [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it has already been demonstrated during the pandemic, in large population studies, severe lung damage and respiratory failure, as well as excessive inflammation, is linked to longer hospital stay and worse outcomes [ 38 , 72 , 73 , 74 , 75 , 76 , 77 ], which is in concordance with our results. Our study revealed that glycemic dysregulation on admission or during hospitalization, as well as higher levels of TRG/HDL-C ratio and TyG index, were associated with prolonged hospital stay.…”
Section: Discussionsupporting
confidence: 93%
“…In parallel with childhood overweight and obesity, the COVID-19 pandemic might exacerbate the condition of DM. The COVID-19 outbreak has caused new challenges in the management of DM, especially for patients with type 2 DM [ 4 ]. Preliminary studies have shown that in countries that have introduced lockdowns, treatment delays and interruption of treatment, services, and medication supplies in DM patients have occurred.…”
mentioning
confidence: 99%